Service Performance of Indonesian Private Hospitals: An Empirical Study Using the SERVPERF and IPA Approach - Setyaningsih, Ira; Widagdo, Muhammad Beny Fahri (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2023)
Patient perceptions have become an important component in determining the quality of a hospital’s service. This study attempts to analyze hospital performance from the customer perspective by adopting the SERVPERF method through five variables, namely tangibles, reliability, assurance, responsiveness, and empathy, with the aim of identifying and recommending areas that the hospital needs to focus on. A total of 100 respondents as outpatients were involved in this study. The cross-sectional survey was conducted online using Google Forms during the pandemic in 2020. According to the research findings, the hospital's overall performance is 4.24. Three indicators with low performance but high importance were examined using IPA. A fishbone diagram is used to identify the source of these indicators and to be the reason to propose recommendations. The study is limited to outpatient care departments from a private hospital in Yogyakarta, Indonesia. However, its findings have important implications for hospital managers for measuring their performance from the patients' perspective.